2006
DOI: 10.1002/jcla.20148
|View full text |Cite
|
Sign up to set email alerts
|

Switching from HPLC/UV to MEIA for whole blood sirolimus quantitation: comparison of methods

Abstract: Sirolimus is a immunosuppressive agent for renal transplant recipients. Monitoring of whole blood sirolimus concentration is necessary in order to improve clinical outcomes. An increasing number of clinical laboratories (4-14% during 2005) are using microparticle enzyme immunoassay (MEIA) for sirolimus quantitation but previous reports indicated a high variability, with a mean difference of 17% for MEIA method vs. high-performance liquid chromatography/ultraviolet (HPLC/UV). This study was aimed at comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Although some authors have found similar results using MEIA and HPLC ( 7 , 8 , 10 , 12 ), it is generally accepted that the MEIA leads to an overestimation of the sirolimus concentration in patients’ samples, related to the antibody reacting with hydroxyl- and desmethyl-sirolimus metabolites ( 4 6 , 9 , 11 , 13 , 25 ). The FPIA and MEIA assays provided similar results, with a high correlation coefficient between them, and a standard error of the estimate only slightly higher than the acceptable value ( Figure 1 E).…”
Section: Discussionmentioning
confidence: 92%
“…Although some authors have found similar results using MEIA and HPLC ( 7 , 8 , 10 , 12 ), it is generally accepted that the MEIA leads to an overestimation of the sirolimus concentration in patients’ samples, related to the antibody reacting with hydroxyl- and desmethyl-sirolimus metabolites ( 4 6 , 9 , 11 , 13 , 25 ). The FPIA and MEIA assays provided similar results, with a high correlation coefficient between them, and a standard error of the estimate only slightly higher than the acceptable value ( Figure 1 E).…”
Section: Discussionmentioning
confidence: 92%